2017
DOI: 10.1021/acs.chemmater.7b01449
|View full text |Cite
|
Sign up to set email alerts
|

Reactive AgAuS and Ag3AuS2 Synthons Enable the Sequential Transformation of Spherical Nanocrystals into Asymmetric Multicomponent Hybrid Nanoparticles

Abstract: Nanoscale heterostructures that interface with multiple distinct materials provide opportunities to engineer functional complexity into single-particle constructs. However, existing synthetic pathways to such hybrid nanoparticles emphasize surface-seeded growth, which limits the scope of accessible systems. Here, we introduce an alternative approach that transforms isotropic nanocrystals into asymmetric, multicomponent Janus particles through sequential deposition, reactive phase segregation, and cation exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…In addition, since a higher pH value also makes glycine a stronger reductant in the first step, the reduction of Ag could be boosted up, and the thickness of Ag wetting layers would increase with pH value of the reaction solution. As a result, more Se atoms are allocated to the process of Ag layer selenization and CdSe growth at high pH environment, which will prolong the Ag 2 Se ripening time and ease the AuAg interfacial etching [48]. Our experiment conducted at different pH environments also confirmed this argument.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, since a higher pH value also makes glycine a stronger reductant in the first step, the reduction of Ag could be boosted up, and the thickness of Ag wetting layers would increase with pH value of the reaction solution. As a result, more Se atoms are allocated to the process of Ag layer selenization and CdSe growth at high pH environment, which will prolong the Ag 2 Se ripening time and ease the AuAg interfacial etching [48]. Our experiment conducted at different pH environments also confirmed this argument.…”
Section: Resultssupporting
confidence: 72%
“…Then, it is inevitable that Se 0 will continue to etch the AuAg alloyed interface. The metal-semiconductor interfaces would further flatten along a certain crystal plane [48]. Meanwhile, the corresponding semiconductor bumps gradually enlarge, as displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the field of multiphase, polyelemental NPs progresses toward greater compositional diversity and structural complexity (1,2,(18)(19)(20)(21), understanding how specific classes of interfaces can be established in one particle is crucial for designing new and functional nanostructures. Although NPs have been synthesized and characterized with up to four phases (1,2,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), there is limited general understanding of why specific architectures form, and the role of surface and interfacial energies in controlling the architecture of NPs with more than two phases is not fully understood.…”
mentioning
confidence: 99%
“…One of the important observations noticed here was the expected Au(I) ion segregation which was expected due to Ag(I) exchanging with other bivalent or trivalent cations. In the previous report by Li et al, it was observed that the composition of Au and Ag in AuAgS varied where amount of Au(I) increased with time as Ag(I) ions were exchanged. This was clearly reflected from the change in XRD patterns.…”
Section: Resultsmentioning
confidence: 90%